Integrasi Nilai Religius dan Teori Agensi dalam Akuntabilitas Pengelolaan Dana Desa di Indonesia: Sebuah Kajian Sistematis (Systematic Literature Review 2015-2025) - Nur Aulia; Muji Burrohman; Mahameru Rosy Rochmatullah (Politeknik Ganesha Medan, 2026)
The management of village funds in Indonesia continues to face significant challenges related to accountability and transparency, as highlighted by repeated findings from the Audit Board of Indonesia (BPK) and the Corruption Eradication Commission (KPK). This study aimed to explore how the integration of religious values within the agency theory framework can strengthen accountability mechanisms and mitigate agency conflicts in village fund management. The results of this systematic literature review (SLR) indicate that religious values such as honesty, trustworthiness (amanah), and spiritual responsibility play a critical role in reinforcing public trust in village governance. These values function as internalized moral standards that limit opportunistic behavior through self-regulation and reduce moral hazard. By embedding such values into the agency framework, village officials are not solely guided by formal control mechanisms, such as regulations, audits, and reporting systems, but also by moral accountability derived from religious and cultural norms. The proposed Moral Accountability Model conceptualizes this dual-control system, aligning formal institutional oversight with informal moral guidance. This model suggests that sustainable accountability is achieved not merely through external enforcement but also through internalized ethical awareness, which fosters holistic, ethical, and legitimate governance. The integration of religiosity into agency mechanisms provides a practical pathway to reduce agency costs and enhance governance quality, particularly in contexts where formal monitoring may be limited or ineffective. Furthermore, the evidence mapping across 22 national and international studies (2015–2025) demonstrates consistent support for the role of moral-religious values in improving transparency, trust, and responsible decision-making. These findings highlight the necessity of harmonizing formal regulatory frameworks with culturally embedded moral norms to achieve accountable and sustainable village fund management. The study contributes theoretically by extending agency theory into the moral-religious domain and practically by offering a model that can guide policymakers and local governments in enhancing governance outcomes.